Multiteaching style and active reflection for swimming - Signorini, Gabriele; Scurati, Raffaele; Formenti, Damiano; Trecroci, Athos; Merati, Giampiero; Del Bianco, Roberto; Rigon, Marta; Invernizzi, Pietro Luigi (Frontiers in Sports and Active Living, 2025)
A student-centred approach is widely used in team sports, but less so in swimming. A proper dosage of stimuli and a multiteaching approach, where games can link understanding and motor competence, could lead to educational success. This study investigated the didactical, methodological, and personal competencies of swimming instructors (SI) and their relationships with children's actual and perceived aquatic competencies. Two hundred children and 44 SI participated in the study. The Teaching Styles Questionnaire (TSQ) assessed the instructors' self-reported awareness of the teaching styles they use, which was compared with the experimenters' observations (as recorded by IESPES, System for Observing Fitness Instruction Time, and Instrument for Identifying Teaching Styles tools). The instructors' empathy and self-control were further evaluated, while two pictorial scales assessed the children's actual and perceived aquatic competence. TSQ confirmed the instructors' predominant use of monoteaching pedagogy, primarily characterized by linear (command and practice) styles (p < 0.001; W = 0.71). Even if SI exhibited general positive personal skills (empathy and self-control), a discrepancy between children's actual and perceived aquatic competence was found (p < 0.001; r = −0.83), with the latter overestimating the former. Conversely, the multiteaching approach of instructors directly correlated with didactic effectiveness (r = 0.64), empathy (r = 0.75), and children's actual (r = 0.63) and perceived aquatic competence (r = 0.65), suggesting that a multiteaching approach should also be used in swimming.